The hearth in the medieval dwelling of Ani - Baeva, Olga (project baikal, 2024)
Based on field studies, historiographical data and materials published by Russian and Turkish archaeologists, the article studies the peculiarities of arrangement and location of tonirs and fireplaces – the main types of hearths discovered in dwellings of the ancient settlement. The revealed prototypes and analogues allowed to draw conclusions about the stability of these types in the culture of the Near and Middle East, as well as to raise questions about the sources of origin of Ani fireplaces and to put forward a hypothesis that it is possible to speak about the outlined process of transition of sacral hearths into the sphere of households.